Middle School Teachers' Use of Compulsory Textbooks in Instruction of Mathematics - Ulusoy, Fadime; İncikabı, Lütfi (University of Plymouth, 2020)
This study investigates how a sample of middle school mathematics teachers interpret and use compulsory textbooks in the Turkish classroom context based on their: (i) purposes of using textbooks; (ii) frequency and duration of using textbooks; (iii) approaches to using textbooks; and (iv) preferences concerning an ideal mathematics textbook. The research was carried out using the case study model. Data were collected from 17 middle school teachers in six public schools via semi-structured interviews and classroom observations. A content analysis approach was applied to analyse the data collected from the questionnaire completed by the participants. The results indicated that the teachers used textbooks for both pedagogic purposes and giving student assignments. The teachers revealed varied approaches to using textbooks, including adherence, elaboration, and creation with most of them using an elaboration approach. The teachers commonly used textbooks in whole-class activities rather than individual and group work. The findings also indicated that teachers criticized compulsory textbooks from various aspects when describing an ideal mathematics textbook. This study shows the necessity for further studies that focus on teachers' textbook design capacity to explore the relationships between teachers and textbooks and that examine the role of using different textbooks in the learning process.
Keywords: 4. Education